Poverty and Inequality (London : C. W. Publishing Ltd.)
1944-10 1944 1940s 29 pages 8 schools. Yet 75% per cent. of them would have profited by secondary education, in the opinion of the Departmental Committee on Scholarships and Free Places. The "special place" examination decides a child's fate at the age of 11. Gifted children may be denied secondary education because they were off-colour at the time, because of school missed through illness, because home conditions were unpropitious to their mental efforts, or because they develop late. In contrast, every child of the upper and middle classes, no matter how stupid, receives secondary education. And many wealthy young men whose intelligence is no more than average, are sent to Oxford or Cambridge, not so much for the academic training as for social reasons. (4) Educational Background and the Best Jobs.* Professions. No. for whom Information is available.† Public Schools Privately or abroad. Other Schools. Bishops 56 out of 68 52 4 Deans 24 out of 30 20 4 Lords of Appeal, Justices of Court of Appeal and High Court............ 25 out of 39 19 6 County Court Judges, Recorders, Metropolitan and Stipendiary Magistrates 156 out of 215 131 25 Home Civil Servants (of 20 Departments receiving £1,000 a year and upwards) 210 out of 455 166 44 Members of Indian Civil Service 41 out of 105 35 6 Governors of Dominions ................ 47 out of 65 33 14 Directors of 5 Banks 82 out of 165 70 12 Conservative M.P.'s 302 out of 375 302 ... (5) The New Education Bill and its effect on Inequality. The Education Bill raises the school leaving age from 14 to 15, and it is intended at an unspecified date to raise it to 16. It introduces secondary education for all, and abolishes fees in all schools maintained or aided by local authorities. It therefore gives the elementary school child a much better chance. He will no longer decide his whole career by an examination taken at the age of 11. It lowers the barrier between middle-class and working-class education. But upper-class education is as aloof and unattainable as ever. The "public schools" remain untouched, still charging enormous fees, still conditioning their products to be "leaders" by virtue only of their birth and wealth, still claiming for them the cream of the available jobs. * Adapted from p. 288 of by R.H. Tawney. The Figures are for 1927 except in the case of M.P.'s, where the figures are for 1938, and adapted from Tory M.P., by Simon Haxey. † As against total number in category. 15X/2/98/13